Residential, Commercial and Industrial Electrical Systems : Equipment and Selection, Volume 1 - Joshi, Hemant (McGraw-Hill's AccessEngineering., 2008)
Residential, Commercial and Industrial Electrical Systems is a comprehensive coverage on every aspect of design, installation, testing and commissioning of electrical systems for residential, commercial and industrial buildings. This book would serve as a ready reference for electrical engineers as well as bridge the gap between theory and practice, for students and academicians, alike.